Censoring the Spirit of Vatican II in Ireland: The Catholic Archdiocese of Dublin and Reality magazine, 1965–71. Issue 3 (3rd July 2021) - Murray, Peter
Abstract : Irish bishops found themselves part of a conservative minority when the Second Vatican Council embarked on a radical overhaul of the Catholic Church between 1962 and 1965. The Irish Church hierarchy generally implemented the resultant changes in a hesitant and unenthusiastic manner. Criticism of their performance was generally muted but the spirit of Vatican II was not entirely without enthusiastic Irish advocates. REALITY, a Redemptorist monthly with a large and mainly young readership, experienced ongoing conflict with clerical censors in the second half of the 1960s. Material in the Archive of the Dublin Catholic Archdiocese show clashes occuring over ecumenism, Vatican II's new conception of the duties of the Catholic lay person and the issue of whether church teaching ought to be enforced by state law. A complicating factor inhibiting repressive action by the Archdiocese was the links forged by this religious magazine with the secular world of Dublin journalism.